2017
DOI: 10.1097/bsd.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Disc Disease: Long-term Changes in Sagittal Alignment and Their Clinical Implications After Cervical Interbody Fusion Cage Subsidence

Abstract: Until fusion occurs, tantalum cage settlement into the vertebral body is to be expected. Further subsidence could be the result of segmental adaptative changes. Graft subsidence did not affect the clinical outcome in any of our patients during long-term follow-up. The occurrence of dynamical implant subsidence had a positive effect on cervical lordosis, especially at the posterior IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
(9 reference statements)
1
21
1
Order By: Relevance
“…Previous investigations showed that implant subsidence does not have a significant association with clinical outcome after anterior operation. [4,16,22] Our findings corroborated the conclusion of previous investigations. Furthermore, we found that the CSA, C2-C7 SVA distance, and grade of ISI were significantly associated with postoperative outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous investigations showed that implant subsidence does not have a significant association with clinical outcome after anterior operation. [4,16,22] Our findings corroborated the conclusion of previous investigations. Furthermore, we found that the CSA, C2-C7 SVA distance, and grade of ISI were significantly associated with postoperative outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, one research reported that the implant subsidence usually occurred at the posterior upper endplates of the caudal bodies. [22] We thought the cause was the function of head gravity center. Historically, T1 slope angle was related to the cervical sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…The ACDF directly removes the anterior compression lesion and increases the height of the neural foramen, which also results in the indirect decompression [ 33 ]. However, graft failures, such as subsidence and pseudarthrosis have been reported frequently [ 12 , 34 , 35 ], which may diminish the effectiveness of indirect decompression and resulted in the recurrence of symptoms [ 35 ]. Our recent study reported that subsidence was associated with PRE T1s [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because these parameters are of significance in predicting the changes that occur when the balance between gravity and force of extension from the posterior neck muscle is disturbed, these factors have been predominantly studied in laminoplasty (LP), a procedure that severely invades the posterior neck muscular-ligament complex [ 4 - 8 ]. Because anterior cervical discectomy and fusion (ACDF) does not damage the posterior neck muscular-ligament complex, studies regarding the influence of preoperative parameters are limited; however, several studies have focused on preoperative C2–7 cervical angle (CA) [ 9 - 12 ]. Recently, Kwon et al [ 13 ] approached post-ACDF cervical alignment using T1 slope (T1s) and sagittal vertical axis (SVA).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a randomized clinical study by Villavicencio et al,20 the authors showed that the use of lordotically shaped allografts does not increase cervical segmental sagittal alignment in comparison with the parallelly shaped ones. In addition, cage subsidence was common in patients treated without the plate 21,22. The addition of an anterior plate system was considered to reduce the problem that the height tended to return gradually toward preoperative value 23.…”
Section: Discussionmentioning
confidence: 99%